The structure of a dewetting rim with strong slip: the long-time evolution - Evans, P.L.; King, John R.; Münch, A. (Society for Industrial and Applied Mathematics, 2018)
When a thin viscous film dewets from a solid substrate, the liquid forms a characteristic rim near the contact line as the contact line retracts. The shape of the rim and also the retraction rate vary strongly with the amount of slip that occurs at the liquid-solid substrate. If the slip length is very large compared to the thickness of the film, extensional stresses dominate the shear stresses, and the film evolution can be modelled by a thin-film model similar to the ones that occur in freely suspended films, with a correction from the viscous friction due to the large but finite slip. Asymptotic investigation of this model reveals that the rim has an amazingly rich asymptotic structure that moreover changes as the solution passes through four distinct time regimes. This paper continues previous work that focused on the first of these regimes [Evans, King, Münch, AMRX 2006:25262, 2006]. The structure of the solution is analyzed in detail via matched asymptotics and then the predictions for the contact line and profile evolution are compared with numerical results.